2022
DOI: 10.7759/cureus.30368
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapy Rehabilitation for a Chronic Alcoholic Patient With Loculated Pleural Effusion

Abstract: Pleural effusion is the accumulation of extra fluid between the layers of the pleura outside the lungs, also known as water on the lungs. Pleura are thin membranes that lubricate and aid breathing by lining the lungs and the inside of the chest cavity. The pleural space typically contains only a few teaspoons of watery fluid, which enables the lungs to move easily inside the chest cavity when breathing. Several barriers limited the patient's capacity to carry out daily activities successfully and efficiently. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In a study conducted by Sanchez-Ramirez, they studied the effect of various pulmonary rehabilitation services on a patient with a restrictive and obstructive pulmonary condition like a six-minute walk test and health-related quality of life short-form health survey (SF-36) using pulmonary rehabilitation and they found increased in six-minute walk test levels and health-related quality of life (SF-36) scores [ 18 ]. According to a study conducted by Tiwari et al, they found pulmonary rehabilitation adjunct to medical treatment of alcoholic patients with pleural effusion proved to decrease dyspnea with the help of an MMRC scale of dyspnea [ 19 ]. Furthermore, as part of the larger medical team, this case report emphasizes the importance of early intervention, advanced pulmonary rehabilitation, and ongoing monitoring by a skilled physiotherapist.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Sanchez-Ramirez, they studied the effect of various pulmonary rehabilitation services on a patient with a restrictive and obstructive pulmonary condition like a six-minute walk test and health-related quality of life short-form health survey (SF-36) using pulmonary rehabilitation and they found increased in six-minute walk test levels and health-related quality of life (SF-36) scores [ 18 ]. According to a study conducted by Tiwari et al, they found pulmonary rehabilitation adjunct to medical treatment of alcoholic patients with pleural effusion proved to decrease dyspnea with the help of an MMRC scale of dyspnea [ 19 ]. Furthermore, as part of the larger medical team, this case report emphasizes the importance of early intervention, advanced pulmonary rehabilitation, and ongoing monitoring by a skilled physiotherapist.…”
Section: Discussionmentioning
confidence: 99%
“…Post-op rehabilitation begins with close collaboration between the surgeon, medical staff, the patient, and the rehabilitation therapy team following non-union fixation. Nevertheless, it is essential to acknowledge the individual nature of such cases, as factors like age, comorbidities, and overall health status may influence the rehabilitation protocol [ 19 ]. Isometric quadriceps exercises help maintain muscle tone and prevent atrophy in the context of an infected non-union without putting undue strain on the healing site.…”
Section: Discussionmentioning
confidence: 99%
“…There are various treatments available, like the Ilizarov fixator, plating, and intramedullary nailing fixation using open reduction internal fixation through non-union [ 17 , 18 ]. Physiotherapy also plays a key role in rehabilitating the patient and making their recovery in a safe and quicker manner [ 19 ].…”
Section: Introductionmentioning
confidence: 99%